Primeri prostorskih analiz vplivov podnebnih sprememb: Monografija v okviru projekta Preprečevanje toplotnega stresa v urbanih sistemih v luči podnebnih sprememb (ARRS J7-1822) (University of Maribor Press, 2022)
Case Studies of Climate Change Effects Spatial Analysis: A monograph Based on Findings from the Project Preventing Heat Stress in Urban Systems Under Climate Change (ARRS J7-1822). In the period of digital transformation of society, information technologies are gaining in importance. This includes geographic information systems that link location data to all types of descriptive information, thus providing a basis for mapping and spatial analysis. The latter is used today in both science and industry. With the help of this type of analysis, it is easier to understand past and present spatial patterns that are the result of the interaction of natural and social conditions. Based on the recognized trends, we can then estimate what the further spatial development will be. The ability to predict objectively is one of the key features that further increases the usefulness of spatial analysis in terms of evaluating the consequences of climate or environmental crisis. This fact is the reason for the creation of the monograph entitled Case Studies of Climate Change Effects Spatial Analysis. The publication is divided into three chapters. The first deals with urban environments and addresses the issue of increasing heat stress as a consequence of the emergence of urban heat island effect (UHI) and a warmer atmosphere due to (anthropogenically driven) climate change. The second chapter deals with the effects of climate change on selected habitats of the cultural landscape, whether in intensive or extensive agricultural use. In the third chapter, the content shifts from terrestrial to costal and marine environments.